Transformative Leadership Management In Islamic Educational Institutions - Budiman (CV Putra Publisher, 2023)
Transformative leadership is leadership that has insight into the future and seeks to improve and develop the organization not for the present, but for the future. Transformative leadership is always committed to continuous improvement, which is based on foresight (better organizational conditions), and encourages the participation of its staff to realize the expected changes. In improving the quality of Islamic education institutions, it is necessary to make fundamental changes in the aspect of leadership, namely by applying a transformational leadership style. The results of the analysis of this study indicate that transformative leadership that can influence Islamic educational institutions will have a good impact on developing organizational productivity, where the vision and mission of the institution will be achieved effectively. This is because transformative leaders can become figures and leaders who inspire organizations to maximize member loyalty.